2020
DOI: 10.1111/sms.13864
|View full text |Cite
|
Sign up to set email alerts
|

Aiming strategy affects performance‐related factors in biathlon standing shooting

Abstract: To investigate differences in shooting performance and performance related factors between the HOLD and the TIMING strategy in biathlon standing shooting. Both groups demonstrated similar shooting performance both at REST and in RACE. In HOLD, better shooting performance was related to higher holding time (HT) REST r=-0.88, p=0.001 RACE r=-0.73, p=0.016 higher aiming accuracy (COG) REST r=0.93, p<0.001 RACE r=0.72, p=0.018 (Figure 3). In TIMING, better shooting performance was related to lower mean velocity (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…As in air rifle shooting, 10 both variables were related to shooting performance in this study. In the biathlon standing shooting study, 9 both variables were related to shooting performance in biathletes using the hold strategy for aiming. In contrast, neither variable was related to performance in biathletes using the timing strategy 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in air rifle shooting, 10 both variables were related to shooting performance in this study. In the biathlon standing shooting study, 9 both variables were related to shooting performance in biathletes using the hold strategy for aiming. In contrast, neither variable was related to performance in biathletes using the timing strategy 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In the biathlon standing shooting study, 9 both variables were related to shooting performance in biathletes using the hold strategy for aiming. In contrast, neither variable was related to performance in biathletes using the timing strategy 9 . Thus, it could be suggested that biathlon prone shooting could be technically similar to the hold strategy in biathlon standing shooting and precision shooting (e.g., air rifle shooting).…”
Section: Discussionmentioning
confidence: 99%
“…Successful shots are further characterized by being fired at a specific phase of the cardiac cycle (under exercise conditions less frequently from 100 to 200 ms after the R-wave; Gallicchio et al, 2019 ). Dependent on the aiming strategy (the so-called hold vs. timing strategy), shooting accuracy is associated with more stable aiming at the center of the target and a decrease in total velocity of the rifle just before firing the shot (Köykkä et al, 2020 ). Finally, some research focused on the impact of physiological workload on shooting performance, revealing equivocal findings: Some studies showed deteriorations in shooting accuracy with increasing workload (Hoffman et al, 1992 ; Grebot et al, 2003 ; Vickers and Williams, 2007 ; Ihalainen et al, 2018 ), while other studies indicate no effects (Gallicchio et al, 2016 ; Luchsinger et al, 2016 ; Heinrich et al, 2020 ).…”
Section: In a Nutshell: Research On Biological Factors Of Biathlon Performancementioning
confidence: 99%
“…Over the past few decades, a growing body of biathlon-specific research considerably improved our understanding of the factors determining biathlon performance (for a review, see Laaksonen et al, 2018 ). This includes biological aspects of biathlon performance, comprising physiological parameters (e.g., Rundell and Bacharach, 1995 ; Stoeggl et al, 2015 ; Laaksonen et al, 2020 ) as well as biomechanical and motor control factors such as postural control, rifle stability, shoulder force, and triggering or aiming strategies (e.g., Groslambert et al, 1999 ; Baca and Kornfeind, 2012 ; Sattlecker et al, 2014 ; Köykkä et al, 2020 ). In addition, another branch of research focuses on psychological factors that influence performance, including the role of attentional processes (e.g., Gallicchio et al, 2016 ; Luchsinger et al, 2016 ; Heinrich et al, 2020 ), dealing with psychological pressure (e.g., Vickers and Williams, 2007 ; Lindner, 2017 ) and the effectiveness of psychological interventions (e.g., Groslambert et al, 2003 ; Laaksonen et al, 2011 ).…”
mentioning
confidence: 99%
“…There was little research on body stability when shooting based strictly on a group that does not conduct regular physical exertion and exercises to improve body stability. Both factors strongly correlate with the deflection amplitude [ 40 ]. The more trained the competitor is, the more experienced the shooter is, the body deflects less, the better the stability and accuracy of the shots are [ 27 , 36 , 41 ].…”
Section: Introductionmentioning
confidence: 99%